The Influence of CHSE Implementation on the Economic Growth Potential Of Halal Tourism with Interest in Returning as a Moderating Variable - Lis Yulitasari; Tulus Suryanto; Syamsul Hilal (International Journal of Economics Development Research (IJEDR), 2023)
As more muslim populations adopt halal lifestyles, the halal industry's growth is still on the rise. The tourism industry has become more aware of halal products, which are no longer limited to food and drink items. Indonesia has emerged as the top-ranked halal travel destination among the Organization of Islamic Cooperation (OIC) nations, according to the 2023 Global Muslim Travel Index (GMTI). Lampung province is one of the thirteen (13) provinces in Indonesia that have been developed to become halal tourism attractions. One of the key industries in Lampung Province that promotes the economic development of the area is tourism. The application of religion and CHSE can make travelers more interested in visiting these places again. The higher the interest of tourists in visiting again, the greater the potential for economic growth in the community. This research aims to determine and analyze the effect of CHSE implementation on the potential economic growth of halal tourism with an interest in returning as a moderating variable. This research uses a quantitative approach with an associative type. This research was conducted at the Liwa Botanical Gardens, West Lampung Regency, in September 2023. The population in this study were all tourists who had visited the Liwa Botanical Gardens, West Lampung Regency, with a sample of 132 people. The sampling technique used was accidental sampling. The instrument used was a questionnaire using Google Form media. Data analysis in this research uses smartPLS (Partial Least Squares). The results of this research show that there is an influence of CHSE implementation on interest in returning to visit. Meanwhile, the indirect interaction test results showed that interest in returning to visit was able to significantly moderate the relationship between CHSE implementation and potential economic growth. The results of this research will provide input for the regional government to create policies regarding regulations for tourist visitors in West Lampung Regency so that tourism can increase regional income for West Lampung Regency.